Establecimiento y zonas productoras del cultivo de la gulupa :(Passiflora edulis f. edulis sims) - Ocampo Pérez, John; Posada Quintero, Paula; Marín, Carlos; López, Nathali; Solano, Rafael (Universidad Jorge Tadeo Lozano, 2018)
Gulupa-Passiflora ligularis